Epidemiological profile of post-exposure patient adherence in northern Brazil (Research, Society and Development, 2022)
This work is entitled Epidemiological Profile of Adherence of Post-Exposure Patients in the Northern Region of Brazil, where the aim was to search for a total of people who started a PEP treatment (post-exposure prophylaxis), to verify the adherence to PEP and to describe the profile epidemiological profile of patients with indication for PEP from 2018 to 2022. For this, we defined as a general objective to determine the epidemiological profile of patients exposed to the HIV virus with adherence to PEP in the northern region of Brazil. The main author who based this research was the website of the Ministry of Health, where the general number of patients who used PEP is stored. The type of research to emphasize the work as its introduction and its development was bibliographic research carried out electronically, through consultation of scientific articles. What made it possible to point out that the profile of people who seek PEP is made up of health professionals (occupational accident), and people who relate to several partners and without using condoms (sexual exposure).